Critical Review on Pharmaceutical vistas of Mandura kalpa (Hematinics of Ayurveda) - K.L, Virupaksha Gupta (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIron is an essential trace metal in the human body. Its inadequacy leads to Iron Deficiency Anemia. Contemporary medical science prescribes ferrous salts for the treatment of anemia. These tend to induce some adverse effects. Hence, Mandura Kalpas are an alternative and are noteworthy iron formulations of Ayurveda. Literary search of different Ayurvedic Classics (Bhaishajya Ratnavali, Charaka Samhita, Ashtanga Hridaya, Chakradatta etc.) reveals many Mandura Kalpas which are found to be therapeutically significant. Most of the formulations are prepared by Rasakriya method and few of them by Khalviya and other methods. Many of the formulations are processed in cow urine. Hence some beneficial role of cow urine in the iron metabolism has been anticipated. This study critically review’s the Mandura kalpas (Hematinics) of Ayurveda and it also identifies the need for further research on the role of cow urine in iron metabolism.